Selective Hydrogenation of 5-Hydroxymethylfurfural to 2,5-Dimethylfuran Over Popcorn-Like Nitrogen-Doped Carbon-Confined CuCo Bimetallic Catalyst - Hao, Peng; Zuo, Jianliang; Tong, Wurong; Lin, Jing; Wang, Qiying; Liu, Zili (Frontiers in Chemistry, 2022)
A new type of biomass-based liquid fuel, 2,5-dimethylfuran (DMF), has attracted significant attention owing to its unique physical properties and carbon neutrality. It can be obtained from the conversion of 5-hydroxymethylfurfural (HMF), an important biomass platform compound. In this study, we developed a nitrogen-doped carbon-confined CuCo bimetallic catalyst with a popcorn-like structure for the selective hydrogenation of HMF with high efficiency and adequate stability. Under optimised conditions, 100% HMF conversion and 93.7% DMF selectivity were achieved. The structure of the CuCo bimetallic catalyst was characterised using XRD, XPS, SEM, and TEM. We observed that carbon spheres, which were covered by nitrogen-doped carbon nanotubes, uniformly formed, while metal particles were confined in the nitrogen-doped carbon nanotubes. The popcorn-like structure exhibited a larger surface area and provided more contact sites, while the confined metal particles were the main active sites. The synergistic effect between Cu and Co was beneficial for DMF selectivity.